Fluorine-containing copolymer
Patent Information
- Application Number
- CN202280016711.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2022-02-28
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-02-28
AI Technical Summary
Existing fluorinated copolymers are difficult to form a uniform and thick coating on the core wire, and the molding speed is slow. They also have insufficient ozone resistance and carbon dioxide permeability, and fluoride ions are easily dissolved into hydrogen peroxide water.
Adjusting the content of hexafluoropropylene units and fluoroalkyl vinyl ether units in the fluorinated copolymer, controlling the melt flow rate and the number of functional groups, and optimizing the molding process such as extrusion molding can form a coating layer of uniform thickness.
It achieves uniform thickness coating molding on the core wire, improves molding speed, enhances ozone resistance, carbon dioxide permeability and tensile creep resistance at 110℃, and reduces fluoride ion leaching.
Smart Images

Figure BDA0004409386260000071 
Figure BDA0004409386260000191 
Figure BDA0004409386260000251
Abstract
Description
Technical Field
[0001] This invention relates to fluorinated copolymers. Background Technology
[0002] Patent Document 1 discloses a melt-processable composition, which is a melt-processable perfluorinated polymer composition comprising: a) a melt-processable perfluorinated polymer, said perfluorinated polymer comprising (i) 80-98 wt% repeating units derived from tetrafluoroethylene, (ii) 2-20 wt% repeating units derived from hexafluoropropylene, and (iii) 0-5 wt% repeating units derived from other comonomers besides tetrafluoroethylene and hexafluoropropylene, wherein the weight proportion of repeating units derived from hexafluoropropylene units is greater than the weight proportion of repeating units of said other comonomers; and
[0003] b) A high molecular weight perfluorinated polymer having a melting point at least 20°C higher than that of the fluorinated polymer a), with a melting point of 0.01 to 5% by weight, based on the perfluorinated polymer a).
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Publication No. 2004-502853 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] The purpose of this invention is to provide a fluorinated copolymer that can form a very thick coating layer with uniform thickness on a core wire with a very large diameter, resulting in a beautiful tube, and can be molded into a film with uniform thickness at a high molding speed, resulting in a molded body with excellent ozone resistance, carbon dioxide permeability, tensile creep resistance at 110°C, excellent creep resistance, and fluoride ions that are not easily dissolved in hydrogen peroxide water.
[0009] Methods for solving problems
[0010] According to the present invention, a fluorinated copolymer is provided, comprising tetrafluoroethylene units, hexafluoropropylene units, and fluorinated (alkyl vinyl ether) units, wherein the content of hexafluoropropylene units is 5.0% to 7.5% by mass relative to all monomer units, the content of fluorinated (alkyl vinyl ether) units is 0.8% to 2.9% by mass relative to all monomer units, and the melt flow rate at 372°C is 0.7 g / 10 min to 9.5 g / 10 min, per 10 6 The number of main chain carbon atoms and the number of functional groups are less than 90.
[0011] The content of hexafluoropropylene units relative to all monomer units is preferably 5.2 to 7.2% by mass.
[0012] The content of fluorinated (alkyl vinyl ether) units is preferably 1.2% to 2.2% by mass relative to all monomer units.
[0013] The melt flow rate at 372℃ is preferably 0.7 to 8.0 g / 10 min.
[0014] The fluorinated (alkyl vinyl ether) unit is preferably a perfluoro (propyl vinyl ether) unit.
[0015] In addition, according to the present invention, injection molded articles, extruded articles or transfer molded articles containing the above-mentioned fluorinated copolymers are provided.
[0016] In addition, according to the present invention, a coated wire having a coating layer containing the above-mentioned fluorinated copolymer is provided.
[0017] In addition, according to the present invention, a molded body is provided, which is a molded body containing the above-mentioned fluorinated copolymer, wherein the molded body is a gasket, wire coating or film.
[0018] Invention Effects
[0019] According to the present invention, a fluorinated copolymer can be provided, which can form a very thick coating layer with uniform thickness on a core wire with a very large diameter, resulting in a beautiful tube, and can be formed into a film with uniform thickness at a high forming speed, resulting in a molded body with excellent ozone resistance, carbon dioxide permeability, tensile creep resistance at 110°C, excellent creep resistance, and fluoride ions that are not easily dissolved in hydrogen peroxide water. Detailed Implementation
[0020] The following describes specific embodiments of the present invention in detail, but the present invention is not limited to the following embodiments.
[0021] The fluorinated copolymer of the present invention contains tetrafluoroethylene (TFE) units, hexafluoropropylene (HFP) units, and fluorinated (alkyl vinyl ether) (FAVE) units.
[0022] Patent Document 1 describes a method of mixing a high-melting-point (i.e., a higher melting point than the melt-processable perfluoropolymer) and a high-molecular-weight (i.e., a larger molecular weight than the melt-processable perfluoropolymer) fluoropolymer in a small proportion with a fluoropolymer containing high melting point and high molecular weight. The resulting material generally exhibits improved mechanical properties compared to existing FEP polymers. Bending fatigue strength was evaluated as one of these mechanical properties in Patent Document 1. However, conventional fluoropolymers have insufficient ozone resistance, and cracks sometimes form in the molded articles when exposed to ozone.
[0023] It was discovered that by adjusting the content of HFP and FAVE units, melt flow rate, and number of functional groups in fluorinated copolymers containing TFE, HFP, and FAVE units to extremely limited ranges, the moldability of the fluorinated copolymers is improved, and molded articles with excellent ozone resistance can be obtained. Furthermore, it was found that the resulting molded articles exhibit excellent carbon dioxide permeability, tensile creep resistance at 110°C, and creep resistance, making it difficult for fluoride ions to dissolve in hydrogen peroxide water. Therefore, when the fluorinated copolymers of the present invention are used as gaskets, for example, in non-aqueous electrolyte batteries, sufficient sealing can be ensured, while simultaneously improving the carbon dioxide permeability of the gasket, allowing internally generated carbon dioxide to pass through to the outside, resulting in a battery that does not easily retain carbon dioxide internally.
[0024] Furthermore, by using extrusion molding to form the fluorinated copolymer of the present invention, a very thick coating layer with uniform thickness can be formed on core wires with very large diameters, resulting in beautiful tubes, and it is also possible to form a film of uniform thickness at high molding speeds. Thus, the fluorinated copolymer of the present invention can be used in a wide range of applications such as gaskets, wire coatings, and films.
[0025] The fluorinated copolymer of the present invention is a melt-processable fluoropolymer. Melt processability refers to the ability to melt and process the polymer using existing processing equipment such as extruders and injection molding machines.
[0026] As a FAVE constituting the above-mentioned FAVE unit, at least one of the groups consisting of the monomers shown in general formula (1) and the monomers shown in general formula (2) can be listed.
[0027] General formula (1):
[0028] CF2 = CFO(CF2CFY) 1 O) p -(CF2CF2CF2O) q -Rf (1)
[0029] (where Y) 1 (This indicates F or CF3, Rf indicates a perfluoroalkyl group with 1 to 5 carbon atoms, p indicates an integer from 0 to 5, and q indicates an integer from 0 to 5.)
[0030] General formula (2):
[0031] CFX = CXOCF2OR 1 (2)
[0032] (In the formula, X being the same or different represents H, F, or CF3, R) 1This refers to a straight-chain or branched fluoroalkyl group having 1 to 6 carbon atoms and containing 1 to 2 atoms selected from the group consisting of H, Cl, Br, and I; or a cyclic fluoroalkyl group having 5 or 6 carbon atoms and containing 1 to 2 atoms selected from the group consisting of H, Cl, Br, and I.
[0033] Among them, the monomer represented by general formula (1) is preferred as the FAVE, more preferably at least one of the group consisting of perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) (PEVE) and perfluoro(propyl vinyl ether) (PPVE), further preferably at least one of the group consisting of PEVE and PPVE, and particularly preferably PPVE.
[0034] The content of HFP units in the fluorinated copolymer is 5.0 to 7.5% by mass relative to all monomer units, preferably 5.1% by mass or more, more preferably 5.2% by mass or more, preferably 7.4% by mass or less, more preferably 7.3% by mass or less, further preferably 7.2% by mass or less, even more preferably 7.0% by mass or less, particularly more preferably 6.8% by mass or less, especially preferably 6.2% by mass or less, and most preferably 6.0% by mass or less. If the content of HFP units is too high, a molded article with excellent tensile creep resistance at 110°C and excellent creep resistance cannot be obtained; if the content of HFP units is too low, a molded article with excellent ozone resistance and carbon dioxide permeability cannot be obtained.
[0035] The content of FAVE units in the fluorinated copolymer is 0.8 to 2.9% by mass relative to all monomer units, preferably 0.9% by mass or more, more preferably 1.0% by mass or more, further preferably 1.1% by mass or more, even more preferably 1.2% by mass or more, particularly preferably 1.5% by mass or more, especially preferably 1.6% by mass or more, most preferably 1.7% by mass or more, preferably 2.7% by mass or less, more preferably 2.6% by mass or less, further preferably 2.5% by mass or less, even more preferably 2.4% by mass or less, especially preferably 2.3% by mass or less, particularly preferably 2.2% by mass or less, and most preferably 2.0% by mass or less. By keeping the content of FAVE units within the above-mentioned range, a molded article with excellent ozone resistance, carbon dioxide permeability, tensile creep resistance at 110°C, and creep resistance, and with fluoride ions difficult to dissolve in hydrogen peroxide water, can be obtained. When the content of FAVE units is too low, a molded article with excellent ozone resistance and carbon dioxide permeability cannot be obtained.
[0036] The content of TFE units in the fluorinated copolymer is preferably 90.1 to 94.2% by mass relative to all monomer units, more preferably 89.7% by mass or more, more preferably 90.2% by mass or more, further preferably 90.3% by mass or more, even more preferably 90.6% by mass or more, particularly preferably 91.5% by mass or more, most preferably 91.8% by mass or more, preferably 94.2% by mass or less, more preferably 94.0% by mass or less, further preferably 93.9% by mass or less, even more preferably 93.7% by mass or less, and particularly preferably 93.6% by mass or less. Alternatively, the content of TFE units can be selected such that the total content of HFP units, FAVE units, TFE units, and other monomer units is 100% by mass.
[0037] The fluorinated copolymer of the present invention can be a copolymer containing only the above-mentioned three monomer units, or it can be a copolymer containing the above-mentioned three monomer units and other monomer units, as long as it contains the above-mentioned three monomer units.
[0038] As for other monomers, there are no particular limitations as long as they can copolymerize with TFE, HFP, and FAVE. They can be either fluorinated or non-fluorinated monomers.
[0039] As a fluorinated monomer, it is preferably selected from trifluorochloroethylene, vinylidene fluoride, vinylidene fluoride, trifluoroethylene, hexafluoroisobutylene, CH2=CZ. 1 (CF2) n Z 2 (where Z) 1 For H or F, Z 2 The monomers shown are H, F, or Cl, where n is an integer from 1 to 10, CF2=CF-O-CH2-Rf 2 (where Rf) 2 It is at least one of the following groups: alkyl perfluorovinyl ether derivatives (represented by a perfluoroalkyl group having 1 to 5 carbon atoms), perfluoro-2,2-dimethyl-1,3-dioxacyclopentene [PDD], and perfluoro-2-methylene-4-methyl-1,3-dioxacyclopentane [PMD].
[0040] As CH2=CZ 1 (CF2) n Z 2 Examples of the monomers shown include CH2=CFCF3, CH2=CH-C4F9, and CH2=CH-C6F. 13 CH2=CF-C3F6H, etc.
[0041] Examples of non-fluorinated monomers include hydrocarbon monomers that can copolymerize with TFE, HFP, and FAVE. Examples of hydrocarbon monomers include: olefins such as ethylene, propylene, butene, and isobutylene; alkyl vinyl ethers such as ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, isobutyl vinyl ether, and cyclohexyl vinyl ether; vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl valerate, vinyl pentanoate, vinyl hexanoate, vinyl octanoate, vinyl decanoate, vinyl tert-carbonate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl benzoate, p-tert-butylbenzoate, vinyl cyclohexanecarboxylate, and vinyl monochloroacetate. Vinyl esters such as vinyl adipate, vinyl acrylate, vinyl methacrylate, vinyl crotonate, vinyl sorbate, vinyl cinnamate, vinyl undecenoate, vinyl glycolate, vinyl hydroxypropionate, vinyl hydroxybutyrate, vinyl hydroxyvalerate, vinyl hydroxyisobutyrate, and vinyl hydroxycyclohexanecarboxylate; alkyl allyl ethers such as ethyl allyl ether, propyl allyl ether, butyl allyl ether, isobutyl allyl ether, and cyclohexyl allyl ether; and alkyl allyl esters such as ethyl allyl ester, propyl allyl ester, butyl allyl ester, isobutyl allyl ester, and cyclohexyl allyl ester.
[0042] As non-fluorinated monomers, they can also be hydrocarbon monomers containing functional groups capable of copolymerizing with TFE, HFP, and FAVE. Examples of hydrocarbon monomers containing functional groups include hydroxyalkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, hydroxyisobutyl vinyl ether, and hydroxycyclohexyl vinyl ether; non-fluorinated monomers with glycidyl groups such as glycidyl vinyl ether and glycidyl allyl ether; non-fluorinated monomers with amino groups such as aminoalkyl vinyl ether and aminoalkyl allyl ether; non-fluorinated monomers with amide groups such as (meth)acrylamide and hydroxymethylacrylamide; bromine-containing alkenes, iodine-containing alkenes, bromine-containing vinyl ethers, and iodine-containing vinyl ethers; and non-fluorinated monomers with nitrile groups.
[0043] The content of other monomer units in the fluorinated copolymer of the present invention is preferably 0 to 4.1% by mass relative to all monomer units, more preferably 1.0% by mass or less, further preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less.
[0044] The melt flow rate (MFR) of the fluorinated copolymer is 0.7 to 9.5 g / 10 min, preferably 0.9 g / 10 min or more, more preferably 1.0 g / 10 min or more, further preferably 1.5 g / 10 min or more, even more preferably 2.0 g / 10 min or more, particularly more preferably 3.5 g / 10 min or more, especially preferably 4.0 g / 10 min or more, most preferably 5.0 g / 10 min or more, preferably 9.0 g / 10 min or less, more preferably 8.9 g / 10 min or less, further preferably 8.5 g / 10 min or less, even more preferably 8.0 g / 10 min or less, particularly preferably 7.0 g / 10 min or less, and most preferably 6.0 g / 10 min or less. By keeping the MFR of the fluorinated copolymer within the above range, the moldability of the copolymer is improved, and molded articles with excellent ozone resistance, carbon dioxide permeability, tensile creep resistance at 110°C, creep resistance, and fluoride ion leaching into hydrogen peroxide water can be obtained. If the MFR is too high, it will be impossible to obtain molded parts with excellent ozone resistance, carbon dioxide permeability, and creep resistance. If the MFR is too low, the extrusion pressure will become too high, resulting in poor moldability.
[0045] In this invention, the melt flow rate is the value obtained according to ASTM D-1238 using a melt flow index tester G-01 (manufactured by Toyo Seiki Co., Ltd.) as the mass (g / 10 min) of polymer flowing out of a die with an inner diameter of 2 mm and a length of 8 mm every 10 minutes under a load of 5 kg at 372 °C.
[0046] MFR can be adjusted by modifying the type and amount of polymerization initiator and the type and amount of chain transfer agent used in monomer polymerization.
[0047] The fluorinated copolymers of the present invention may or may not have functional groups. Functional groups are those present at the ends of the main chain or side chains of the fluorinated copolymer, or those present in the main chain or side chains. Typical functional groups are -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH.
[0048] 10 of fluorinated copolymers 6 The number of functional groups per carbon atom in the main chain is less than 90. Fluorinated copolymers per 10 6 The number of functional groups per carbon atom in the main chain is more preferably 70 or less, further preferably 50 or less, even more preferably 40 or less, particularly preferably 30 or less, especially preferably 20 or less, and most preferably less than 15. By keeping the number of functional groups in the fluorinated copolymer within the above range, it is possible to obtain a molded article with excellent ozone resistance and difficulty in dissolving fluoride ions in reagents such as hydrogen peroxide water.
[0049] The number of functional groups in a fluorinated copolymer is the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH.
[0050] 10 of fluorinated copolymers 6 The number of -CF2H atoms per main chain carbon atom is preferably 50 or less, more preferably 40 or less, even more preferably 30 or less, even more preferably 20 or less, particularly preferably less than 15, and most preferably less than 10.
[0051] 10 of fluorinated copolymers 6 The total number of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2 and -CONH2 with a number of carbon atoms in the main chain is preferably 80 or less, more preferably 70 or less, further preferably 50 or less, even more preferably 40 or less, especially preferably 30 or less, particularly preferably 20 or less, and most preferably less than 15.
[0052] The identification of the types of functional groups and the determination of the number of functional groups mentioned above can be achieved using infrared spectroscopy.
[0053] Regarding the number of functional groups, specifically, it was determined using the following method. First, the above-mentioned fluorinated copolymer was cold-pressed to produce a film with a thickness of 0.25 mm to 0.30 mm. The film was analyzed by Fourier transform infrared spectroscopy to obtain the infrared absorption spectrum of the above-mentioned fluorinated copolymer, and a differential spectrum was obtained compared with the background spectrum of a fully fluorinated copolymer without functional groups. The number of functional groups in the above-mentioned fluorinated copolymer was calculated from the absorption peaks of specific functional groups shown in the differential spectrum according to the following formula (A). 6 The number of functional groups N per carbon atom.
[0054] N = I × K / t(A)
[0055] I: Absorbance
[0056] K: Correction coefficient
[0057] t: Membrane thickness (mm)
[0058] For reference, the absorption frequencies, molar absorptivity, and correction factors for some functional groups are shown in Table 1. Furthermore, the molar absorptivity was determined using FT-IR measurements of low-molecular-weight model compounds.
[0059] [Table 1]
[0060] Table 1
[0061]
[0062] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are tens of Kaiser (cm⁻¹) lower than those of -CF2H, -COF, free -COOH, and bonded -COOH, -COOCH3, and -CONH2, respectively, as shown in the table. 1 ).
[0063] For example, the number of functional groups in -COF refers to the number of functional groups originating from the absorption frequency of -CF2COF at 1883 cm⁻¹. 1 The number of functional groups derived from the absorption peak at 1840 cm⁻¹ and the absorption frequency originating from -CH₂COF were also analyzed. 1 The total number of functional groups obtained from the absorption peak at the given location.
[0064] Alternatively, the number of -CF2H groups can also be determined using a nuclear magnetic resonance (NMR) apparatus, with the measurement temperature set to (the polymer's melting point + 20) °C. 19 The value was determined by F-NMR analysis and obtained from the peak integral of the -CF2H group.
[0065] Functional groups are those present at the ends of the main chain or side chains of fluorinated copolymers, and those present in the main chain or side chains. The number of functional groups can be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH.
[0066] The aforementioned functional groups are introduced into the fluorinated copolymer, for example, through chain transfer agents or polymerization initiators used in the manufacture of the fluorinated copolymer. For instance, when an alcohol is used as a chain transfer agent, or when a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced to the ends of the main chain of the fluorinated copolymer. Alternatively, the aforementioned functional groups are introduced to the ends of the side chains of the fluorinated copolymer by polymerizing monomers containing functional groups.
[0067] By subjecting the fluorinated copolymer having such functional groups to wet heat treatment, fluorination treatment, or other treatments, a fluorinated copolymer having the number of functional groups within the aforementioned range can be obtained. The fluorinated copolymer of the present invention preferably underwent wet heat treatment or fluorination treatment, and more preferably fluorination treatment. The fluorinated copolymer of the present invention also preferably has a -CF3 terminal group.
[0068] The melting point of the fluorinated copolymer is preferably 255–290°C, more preferably 263–290°C. By having a melting point within the above range, the moldability of the copolymer is further improved, and molded articles with better ozone resistance, carbon dioxide permeability, tensile creep resistance at 110°C, and creep resistance can be obtained.
[0069] In this invention, the melting point can be determined using a differential scanning calorimeter (DSC).
[0070] The carbon dioxide permeability of the fluorinated copolymer is preferably 1350 cm⁻¹. 3 ·mm / (m 2 The fluorinated copolymer of the present invention exhibits excellent carbon dioxide permeability due to the appropriate adjustment of the content of HFP and FAVE units, melt flow rate (MFR), and number of functional groups. Therefore, by using gaskets containing such copolymers, it is possible to obtain a battery that is difficult to retain carbon dioxide.
[0071] In this invention, the carbon dioxide transmission coefficient can be determined under test conditions of 70°C and 0% RH. The specific determination of the carbon dioxide transmission coefficient can be performed using the methods described in the examples.
[0072] The amount of fluoride ions dissolved by the fluorine-containing copolymer of the present invention in the immersion test in hydrogen peroxide water is preferably 4.0 ppm or less by mass, more preferably 3.0 ppm or less, and even more preferably 2.8 ppm or less.
[0073] In this invention, the immersion test in hydrogen peroxide water can be carried out as follows: using a fluorinated copolymer, a test piece with a weight equivalent to 10 molded pieces (15mm×15mm×0.2mm) is prepared. A polypropylene bottle containing the test piece and 15g of 3% hydrogen peroxide aqueous solution is placed in a constant temperature bath at 95°C and left for 20 hours.
[0074] The fluorinated copolymers of the present invention can be manufactured by any of the polymerization methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. In these polymerization methods, the conditions such as temperature and pressure, the polymerization initiator, chain transfer agent, solvent, and other additives can be appropriately set according to the desired composition and amount of the fluorinated copolymer.
[0075] Oil-soluble free radical polymerization initiators or water-soluble free radical initiators can be used as polymerization initiators.
[0076] As an oil-soluble free radical polymerization initiator, it can be a known oil-soluble peroxide, and the following substances can be cited as representative examples:
[0077] Dialkyl percarbonate esters, such as di-n-propyl percarbonate, diisopropyl percarbonate, and disec-butyl percarbonate;
[0078] Peroxide esters such as tert-butyl peroxide isobutyrate and tert-butyl perpentyl peroxide;
[0079] Dialkyl peroxides such as di-tert-butyl peroxide;
[0080] Di[fluoro(or fluorochloro)acyl] peroxides; etc.
[0081] Examples of diacyl peroxides include those represented by [(RfCOO)-]2 (where Rf is a perfluoroalkyl, ω-hydroperfluoroalkyl, or fluorochloroalkyl).
[0082] Examples of di[fluoro(or fluorochloro)acyl]peroxides include, for example, di(ω-hydro-dodecanoyl)peroxide, di(ω-hydro-tetradecanoyl)peroxide, di(ω-hydro-hexadecanoyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluoropentanoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-decanoyl)peroxide, and di(ω-decanoyl)peroxide. Fluorohexyl peroxide, di(ω-chloro-tetrafluorooctanoyl) peroxide, ω-hydro-dodecanoyl-ω-hydrohexadecanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecanoyl) peroxide, di(pentachlorotetrafluorodecanoyl) peroxide, di(undecatrifluorotetrafluorodienoyl) peroxide, etc.
[0083] As a water-soluble free radical polymerization initiator, it can be a known water-soluble peroxide, such as ammonium salts, potassium salts, sodium salts of persulfate, perboric acid, perchloric acid, superphosphoric acid, and percarbonate, as well as tert-butyl maleate peroxide and tert-butyl hydroperoxide. It may also contain reducing agents such as sulfites, in amounts ranging from 0.1 to 20 times that of the peroxide.
[0084] Examples of chain transfer agents include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol, ethanol, and 2,2,2-trifluoroethanol; thiols such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane; and 3-fluorobenzotrifluoride. The amount added varies depending on the chain transfer constant of the compound used, and is typically used in the range of 0.01 to 20 parts by mass relative to 100 parts by mass of solvent.
[0085] For example, when using dialkyl peroxide carbonates, di[fluoro(or fluorochloro)acyl]peroxides, etc., as polymerization initiators, the resulting fluorinated copolymers have excessively high molecular weights, sometimes making it difficult to adjust to the desired melt flow rate. However, chain transfer agents can be used to adjust the molecular weight. Fluorinated copolymers are particularly preferably manufactured by suspension polymerization using chain transfer agents such as alcohols and oil-soluble free radical polymerization initiators.
[0086] Examples of solvents include water and mixtures of water and alcohol. Alternatively, the monomers used in the polymerization of the fluorinated copolymers of this invention can also be used as solvents.
[0087] In suspension polymerization, fluorinated solvents can be used in addition to water. Examples of fluorinated solvents include hydrochlorofluorocarbons such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, and CF2ClCF2CFHCl; chlorofluorocarbons such as CF2ClCFClCF2CF3 and CF3CFClCFClCF3; and perfluoroalkyl hydrocarbons such as perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, and CF3CF2CF2CF2CF2CF3, with perfluoroalkyl hydrocarbons being preferred. From the perspectives of suspension performance and economy, the amount of fluorinated solvent used is preferably 10 to 100 parts by mass relative to 100 parts by mass of the solvent.
[0088] There is no particular limitation on the polymerization temperature, which can be 0 to 100°C. However, if the decomposition rate of the polymerization initiator is too fast, such as when using dialkyl peroxide carbonate, di[fluoro(or fluorochloro)acyl]peroxide, etc., as the polymerization initiator, it is preferable to use a lower polymerization temperature, such as a polymerization temperature range of 0°C to 35°C.
[0089] The polymerization pressure is appropriately determined based on the type and amount of solvent used, vapor pressure, polymerization temperature, and other polymerization conditions, and is typically 0–9.8 MPaG. The polymerization pressure is preferably 0.1 MPaG–5 MPaG, more preferably 0.5 MPaG–2 MPaG, and even more preferably 0.5 MPaG–1.5 MPaG. Furthermore, a polymerization pressure of 1.5 MPaG or higher can improve production efficiency.
[0090] Examples of additives used in polymerization include suspension stabilizers. There are no particular limitations on existing, well-known suspension stabilizers; methylcellulose, polyvinyl alcohol, etc., can be used. When a suspension stabilizer is used, the suspended particles generated by the polymerization reaction are stably dispersed in the aqueous medium. Therefore, even when using a SUS-made reaction tank without anti-adhesion treatment such as a glass liner, the suspended particles are less likely to adhere to the reaction tank. This allows the use of a high-pressure-resistant reaction tank, enabling polymerization under high pressure and improving production efficiency. Conversely, if polymerization is carried out without a suspension stabilizer, and a SUS-made reaction tank without anti-adhesion treatment is used, suspended particles may adhere, reducing production efficiency. The concentration of the suspension stabilizer relative to the aqueous medium can be adjusted appropriately according to the conditions.
[0091] When an aqueous dispersion containing a fluoropolymer is obtained through polymerization, the dried fluoropolymer can be recovered by precipitating, washing, and drying the fluoropolymer contained in the aqueous dispersion. Alternatively, when a fluoropolymer is obtained in slurry form through polymerization, the dried fluoropolymer can be recovered by removing the slurry from the reaction vessel and washing and drying it. Drying allows the fluoropolymer to be recovered in powder form.
[0092] Fluorinated copolymers obtained through polymerization can be granulated. There are no particular limitations on the granulation method; existing known methods can be used. For example, methods such as melt extruding the fluorinated copolymer using a single-screw extruder, twin-screw extruder, or tandem extruder, and then cutting it into granules of a specified length, can be used. The extrusion temperature during melt extrusion needs to be varied depending on the melt viscosity of the fluorinated copolymer and the manufacturing method; preferably, it is between the melting point of the fluorinated copolymer and 20°C to 140°C. There are no particular limitations on the cutting method of the fluorinated copolymer; existing known methods such as wire cutting, thermal cutting, underwater cutting, and sheet cutting can be used. The volatile components in the granules can also be removed by heating (degassing treatment). Alternatively, the granules can be treated by contacting them with warm water at 30°C to 200°C, steam at 100°C to 200°C, or hot air at 40°C to 200°C.
[0093] Fluorinated copolymers obtained through polymerization can also be heated to temperatures above 100°C in the presence of air and water (wetting heat treatment). Examples of wetting heat treatment methods include: using an extruder, supplying air and water while melting and extruding the fluorinated copolymer obtained through polymerization. Wetting heat treatment can convert thermally unstable functional groups such as -COF and -COOH in the fluorinated copolymer into the more thermally stable -CF2H, easily adjusting the total number of -COF and -COOH, as well as the total number of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, and -CONH2 in the fluorinated copolymer to the ranges described above. Besides air and water, heating the fluorinated copolymer in the presence of alkali metal salts can promote the conversion reaction to -CF2H. However, it should be noted that contamination from alkali metal salts should be avoided depending on the intended use of the fluorinated copolymer.
[0094] Fluorinated copolymers obtained by polymerization can also be fluorinated. Fluorination can be carried out by contacting the unfluorinated copolymer with a fluorinated compound. Through fluorination, thermally unstable functional groups such as -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, and -CONH2, as well as thermally stable functional groups such as -CF2H, in the fluorinated copolymer can be converted into the extremely thermally stable -CF3. As a result, the total number of COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2, and -CF2H groups in the fluorinated copolymer can be easily adjusted to the range described above.
[0095] As for fluorine-containing compounds, there are no particular limitations; any fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. Examples of such fluorine radical sources include F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, and fluorinated halogens (e.g., IF5, ClF3).
[0096] Fluorine radical sources such as F2 gas can be 100% concentrated, but from a safety perspective, it is preferable to mix them with an inert gas and dilute them to 5% to 50% by mass before use, and more preferably to 15% to 30% by mass. Examples of such inert gases include nitrogen, helium, and argon; from an economic perspective, nitrogen is preferred.
[0097] The conditions for fluorination are not particularly limited; the molten fluorinated copolymer can be brought into contact with the fluorinated compound. However, it is generally carried out at a temperature below the melting point of the fluorinated copolymer, preferably between 20°C and 220°C, and more preferably between 100°C and 200°C. The fluorination treatment is typically carried out for 1 hour to 30 hours, preferably 5 hours to 25 hours. The preferred method of fluorination treatment is to bring the unfluorinated fluorinated copolymer into contact with fluorine gas (F2 gas).
[0098] The fluorinated copolymer of the present invention can also be mixed with other components as needed to obtain a composition. Other components include fillers, plasticizers, processing aids, mold release agents, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, conductive agents, antistatic agents, ultraviolet absorbers, antioxidants, foaming agents, fragrances, oils, softeners, defluorinated hydrogen agents, etc.
[0099] Examples of fillers include silica, kaolin, clay, organoclay, talc, mica, alumina, calcium carbonate, calcium terephthalate, titanium dioxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, and glass fiber. Examples of conductive agents include carbon black. Examples of plasticizers include dioctyl phthalate and pentaerythritol. Examples of processing aids include carnauba wax, sulfone compounds, low molecular weight polyethylene, and fluorinated additives. Examples of defluorinating agents include organonium and amidines.
[0100] In addition, other polymers besides the fluorinated copolymers mentioned above can also be used as other components. Examples of other polymers include fluoropolymers, fluororubbers, and non-fluorinated polymers, in addition to the fluorinated copolymers mentioned above.
[0101] Examples of methods for manufacturing the above composition include: dry mixing of the fluorinated copolymer with other components; pre-mixing the fluorinated copolymer with other components using a mixer, followed by melt mixing using a kneader, melt extruder, etc.; etc.
[0102] The fluorinated copolymers or the above-described compositions of the present invention can be used as processing aids, molding materials, etc., and are preferably used as molding materials. Additionally, aqueous dispersions, solutions, suspensions, and copolymer / solvent systems of the fluorinated copolymers of the present invention can be used as coatings, or for encapsulation, impregnation, and film casting. However, due to the aforementioned properties, the fluorinated copolymers of the present invention are preferably used as the above-described molding materials.
[0103] The fluorinated copolymer of the present invention or the above composition can also be molded to obtain a molded body.
[0104] The method for molding the above-mentioned fluorinated copolymer or composition is not particularly limited, and examples include injection molding, extrusion molding, compression molding, blow molding, transfer molding, rotational molding, and roll forming. Among these molding methods, extrusion molding, compression molding, injection molding, or transfer molding are preferred, and injection molding, extrusion molding, or transfer molding are more preferred because they can produce molded bodies with high productivity. In other words, as the molded body, an extruded molded body, a compression molded body, an injection molded body, or a transfer molded body is preferred, and injection molded bodies, extruded molded bodies, or transfer molded bodies are more preferred because they can produce molded bodies with high productivity. Injection molded bodies or extruded molded bodies are even more preferred.
[0105] The molded body containing the fluorinated copolymer of the present invention can be, for example, a nut, bolt, joint, membrane, bottle, gasket, wire sheath, tube, hose, pipe, valve, sheet, seal, gasket, can, roller, container, stopcock, connector, filter housing, filter cover, flow meter, pump, wafer carrier, wafer box, etc.
[0106] The fluorinated copolymers, the above-described compositions, or the above-described molded articles of the present invention can be used for, for example, the following applications.
[0107] Food packaging films, lining materials for fluid transport pipelines used in food manufacturing processes, gaskets, sealing materials, thin sheets, and other fluid transport components for food manufacturing equipment;
[0108] Chemical stoppers, packaging films, lining materials for fluid delivery pipelines used in chemical manufacturing processes, gaskets, sealing materials, thin plates, and other reagent delivery components;
[0109] Inner lining components for reagent containers and piping in chemical equipment and semiconductor plants;
[0110] O-rings / pipes / gaskets, valve core materials, hoses, sealing materials, etc. used in the fuel system and peripheral devices of automobiles; hoses, sealing materials, and other fuel delivery components used in the AT system of automobiles.
[0111] The carburetor flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in the engine and peripheral devices of automobiles; brake hoses, air conditioning hoses, radiator hoses, wire sheathing materials, and other automobile components.
[0112] O-rings, tubes, gaskets, valve core materials, hoses, sealing materials, rollers, washers, diaphragms, connectors and other reagent delivery components for semiconductor manufacturing equipment;
[0113] Coating and ink components for coating equipment, such as coating rollers, hoses, tubes, and ink containers;
[0114] Food and beverage conduits, hoses, belts, gaskets, connectors and other food and beverage conveying components, food packaging materials, and glass cooking equipment;
[0115] Pipes, hoses, and other components used for waste liquid transportation;
[0116] Pipes, hoses, and other components used for high-temperature liquid transfer;
[0117] Pipes, hoses and other components used in steam piping;
[0118] Corrosion-resistant tape for piping, such as tape wrapped around the deck of a ship;
[0119] Various coating materials, such as wire coating materials, optical fiber coating materials, transparent surface coating materials and backing agents applied to the light incident side of photovoltaic elements in solar cells;
[0120] The diaphragm and various sliding components such as gaskets in a diaphragm pump;
[0121] Weather-resistant covers for agricultural films, various roofing materials, and sidewalls;
[0122] Interior materials used in the construction industry, and glass-like covering materials such as non-combustible fire-resistant safety glass;
[0123] Lining materials such as laminated steel sheets used in the home appliance industry.
[0124] Further examples of fuel delivery components used in the fuel systems of the aforementioned automobiles include fuel hoses, filler hoses, and evaporator hoses. These fuel delivery components can also be used for fuels resistant to acidic gasoline, alcohol-based fuels, and fuels containing gasoline additives such as those resistant to methyl tert-butyl ether and amines.
[0125] The stoppers and packaging films used for the aforementioned chemicals exhibit excellent resistance to acids and other chemicals. Additionally, anti-corrosion tape wrapped around the piping of chemical equipment can also be cited as a component for transporting the aforementioned reagents.
[0126] Examples of such molded bodies include radiator water chambers for automobiles, reagent tanks, bellows, partitions, rollers, gasoline tanks, waste liquid conveying containers, high-temperature liquid conveying containers, and fish farming and aquaculture tanks.
[0127] Further examples of the molded bodies mentioned above include components used in automobile bumpers, door panels, dashboards, food processing devices, cooking machines, waterproof and oil-proof glass, lighting-related instruments, indicator panels and housings of OA instruments, electrically illuminated signboards, displays, LCD screens, mobile phones, printer chassis, electrical and electronic components, groceries, trash cans, bathtubs, prefabricated bathrooms, exhaust fans, lighting frames, etc.
[0128] The molded articles containing the fluorinated copolymers of the present invention exhibit excellent ozone resistance, carbon dioxide permeability, tensile creep resistance at 110°C, and creep resistance, making them suitable for use in nuts, bolts, joints, gaskets, valves, stopcocks, connectors, filter housings, filter covers, flow meters, pumps, etc. They are particularly suitable for use as piping components (especially valves or joints) in reagent delivery and as flow meter bodies containing reagent flow paths. The piping components and flow meter bodies of the present invention exhibit excellent ozone resistance and shape stability. Therefore, the piping components and flow meter bodies of the present invention are not easily damaged even when repeatedly stressed due to the start, stop, and flow rate changes of reagent flow.
[0129] Molded articles containing the fluorinated copolymer of the present invention exhibit excellent ozone resistance and extremely excellent sealing properties, and are unlikely to leach fluoride ions into reagents such as hydrogen peroxide water. Therefore, they are suitable for use as gaskets, sealing gaskets, and other compressed components. The compressed components of the present invention can be gaskets or sealing gaskets. The gaskets or sealing gaskets of the present invention exhibit excellent ozone resistance and extremely excellent sealing properties, and are unlikely to leach fluoride ions into reagents such as hydrogen peroxide water. On the other hand, due to their excellent carbon dioxide permeability, carbon dioxide generated internally can permeate to the outside.
[0130] The size and shape of the compressed member of the present invention can be appropriately set according to the application and are not particularly limited. The shape of the compressed member of the present invention can be, for example, ring-shaped. In addition, the compressed member of the present invention can have a circular, elliptical, or quadrilateral shape with rounded corners when viewed from above, and has a through hole in its central part.
[0131] The compressed member of the present invention is preferably used as a component for constructing a non-aqueous electrolyte battery. Due to its high sealing performance, the compressed member of the present invention is particularly suitable as a component used in contact with the non-aqueous electrolyte in a non-aqueous electrolyte battery. That is, the compressed member of the present invention can have a liquid-contacting surface for contacting the non-aqueous electrolyte in a non-aqueous electrolyte battery.
[0132] As for non-aqueous electrolyte batteries, there are no particular limitations as long as the battery contains a non-aqueous electrolyte; examples include lithium-ion secondary batteries and lithium-ion capacitors. Furthermore, components constituting non-aqueous electrolyte batteries include sealing components and insulating components.
[0133] The non-aqueous electrolyte is not particularly limited and can be one or more of the following known solvents: propylene carbonate, ethylene carbonate, butyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate. The non-aqueous electrolyte battery may further include an electrolyte. The electrolyte is not particularly limited and can be LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc.
[0134] The compressed component of the present invention can preferably be used as a sealing component such as a sealing gasket or sealing pad, or an insulating component such as an insulating gasket or insulating pad. A sealing component is used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating component is used for electrical insulation. The compressed component of the present invention can also be used for both sealing and insulation purposes.
[0135] The compressed component of the present invention exhibits high sealing performance, making it suitable for use as a sealing component or an insulating component for non-aqueous electrolyte batteries. Furthermore, the compressed component of the present invention, containing the aforementioned fluorinated copolymer, possesses excellent insulating properties. Therefore, when the compressed component of the present invention is used as an insulating component, it securely seals with two or more conductive components, preventing short circuits over a long period.
[0136] The fluorinated copolymer of the present invention can form a very thick coating layer with uniform thickness on core wires with very large diameters by extrusion molding, and is therefore suitable as a material for forming wire coatings. The outer diameter of the wire coated with the coating layer containing the fluorinated copolymer of the present invention remains almost unchanged, thus exhibiting excellent electrical properties.
[0137] The coated wire has a core wire and a coating layer disposed around the core wire containing the fluorinated copolymer of the present invention. For example, the coating layer can be an extruded body formed by melt extrusion molding of the fluorinated copolymer of the present invention onto the core wire. The coated wire is suitable for LAN cables (Ethernet cables), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is particularly suitable for transmission cables such as LAN cables (Ethernet cables) and high-frequency transmission cables.
[0138] The core wire material can be a metallic conductor such as copper or aluminum. The core wire diameter is preferably 0.02 mm to 3 mm. More preferably, the core wire diameter is 0.04 mm or more, even more preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. Even more preferably, the core wire diameter is 2 mm or less.
[0139] Specific examples of core wires include AWG (American wire gauge)-46 (solid copper wire with a diameter of 40μm), AWG-26 (solid copper wire with a diameter of 404μm), AWG-24 (solid copper wire with a diameter of 510μm), and AWG-22 (solid copper wire with a diameter of 635μm).
[0140] The thickness of the coating layer is preferably 0.1 mm to 3.0 mm. The thickness of the coating layer is also preferably less than 2.0 mm.
[0141] Coaxial cables are an example of high-frequency transmission cables. Coaxial cables typically have a structure consisting of an inner conductor, an insulating sheath, an outer conductor layer, and a protective sheath layer layered sequentially from the core to the outer periphery. Molded bodies containing the fluorinated copolymer of the present invention can be suitable as insulating sheaths containing the fluorinated copolymer. The thickness of each layer in the above structure is not particularly limited; typically, the diameter of the inner conductor is about 0.1 mm to 3 mm, the thickness of the insulating sheath is about 0.3 mm to 3 mm, the thickness of the outer conductor layer is about 0.5 mm to 10 mm, and the thickness of the protective sheath is about 0.5 mm to 2 mm.
[0142] The coating may contain air bubbles, which are preferably evenly distributed in the coating.
[0143] The average bubble diameter is not limited, but is preferably 60 μm or less, more preferably 45 μm or less, even more preferably 35 μm or less, even more preferably 30 μm or less, particularly preferably 25 μm or less, and especially preferably 23 μm or less. Furthermore, the average bubble diameter is preferably 0.1 μm or more, more preferably 1 μm or more. The average bubble diameter can be obtained by acquiring an electron microscope image of the wire cross-section, calculating the diameter of each bubble using image processing, and then averaging the results.
[0144] The foaming rate of the coating layer can be 20% or more. More preferably, it is 30% or more, further preferably 33% or more, and even more preferably 35% or more. There is no particular upper limit, for example, 80%. The upper limit of the foaming rate can be 60%. The foaming rate is calculated as ((specific gravity of wire coating material - specific gravity of coating layer) / specific gravity of wire coating material) × 100. The foaming rate can be adjusted appropriately according to the application, for example, by adjusting the gas insertion amount in the extruder described later, or by selecting the type of dissolved gas.
[0145] The coated wire may also have other layers between the core wire and the coating layer, and may further have other layers (outer layers) around the coating layer. If the coating layer contains air bubbles, the wire of the present invention may also be a two-layer structure (outer sheath-foam) with a non-foamed layer inserted between the core wire and the coating layer; a two-layer structure (foam-outer sheath) with a non-foamed layer on the outer layer; and a three-layer structure (outer sheath-foam-outer sheath) with a non-foamed layer on the outer layer of the outer sheath-foam. The non-foamed layer is not particularly limited and may be a resin layer composed of TFE / HFP copolymers, TFE / PAVE copolymers, TFE / ethylene copolymers, vinylidene fluoride polymers, polyolefin resins such as polyethylene [PE], and resins such as polyvinyl chloride [PVC].
[0146] Coated wires can be manufactured, for example, by heating a fluorinated copolymer using an extruder and extruding it onto the core wire while the fluorinated copolymer is in a molten state to form a coating.
[0147] During the formation of the coating layer, the fluorinated copolymer can also be heated, and a gas can be introduced into the fluorinated copolymer while it is in a molten state to form the aforementioned coating layer containing bubbles. The gas can be, for example, dichlorofluoromethane, nitrogen, carbon dioxide, or a mixture of these gases. The gas can be introduced into the heated fluorinated copolymer as a pressurized gas, or it can be generated by mixing a chemical foaming agent into the fluorinated copolymer. The gas dissolves in the molten fluorinated copolymer.
[0148] In addition, the fluorinated copolymer of the present invention is suitable for use as a material in products for high-frequency signal transmission.
[0149] As for the aforementioned high-frequency signal transmission products, there are no particular limitations as long as the product is used for high-frequency signal transmission. Examples include (1) molded boards such as insulating boards for high-frequency circuits, insulating materials for connecting components, and printed wiring boards; (2) molded bodies such as bases and radomes for high-frequency vacuum tubes; and (3) covered wires such as coaxial cables and LAN cables. The aforementioned high-frequency signal transmission products are suitable for use in satellite communication equipment, mobile phone base stations, and other equipment that utilizes microwaves, especially microwaves from 3 GHz to 30 GHz.
[0150] In the above-mentioned high-frequency signal transmission products, the fluorinated copolymer of the present invention is suitable for use as an insulator from the perspective of low dielectric loss tangent.
[0151] As for the molded plate described in (1) above, a printed wiring substrate is preferred from the perspective of obtaining good electrical characteristics. There are no particular limitations on the printed wiring substrate described above; examples include printed wiring substrates for electronic circuits in mobile phones, various computers, and communication devices. As for the molded body described in (2) above, an antenna radome is preferred from the perspective of low dielectric loss.
[0152] The fluorinated copolymer of the present invention can be formed into a film of uniform thickness at a high forming speed by extrusion molding. As a result, the obtained molded body has excellent ozone resistance, carbon dioxide permeability, tensile creep resistance at 110°C and creep resistance, and is therefore suitable for use in films.
[0153] The film of the present invention is useful as a release film. The release film can be manufactured by molding the fluorinated copolymer of the present invention through melt extrusion molding, calendering, compression molding, casting, etc. From the viewpoint of obtaining a uniform film, the release film can be manufactured by melt extrusion molding.
[0154] The membrane of this invention can be applied to the surface of rollers used in OA equipment. Furthermore, the fluorinated copolymer of this invention can be molded into necessary shapes, such as sheets, films, or tubes, through extrusion molding, compression molding, or pressing, for use as a surface material for OA equipment rollers or belts. In particular, thin-walled tubes and membranes can be manufactured using melt extrusion molding.
[0155] The fluorinated copolymer of the present invention can be extruded to obtain beautiful tubes. Furthermore, the resulting molded body exhibits excellent ozone resistance, carbon dioxide permeability, tensile creep resistance at 110°C, and creep resistance, making it suitable for use as a tube. Therefore, tubes containing the fluorinated copolymer of the present invention can be manufactured with high productivity and possess beautiful shapes, excellent ozone resistance, carbon dioxide permeability, tensile creep resistance at 110°C, and creep resistance.
[0156] The embodiments have been described above, but it is understood that various changes can be made to the methods and details without departing from the spirit and scope of the claims.
[0157] Example
[0158] Next, embodiments will be given to illustrate the implementation of the present invention, but the present invention is not limited to the embodiments described.
[0159] The values in the examples were measured using the following methods.
[0160] (Monomer content)
[0161] The content of each monomer unit in the fluorinated copolymer was determined using an NMR analyzer (e.g., Bruker BioSpin, AVANCE300 high-temperature probe) or an infrared absorption analyzer (Perkin Elmer, Spectrum One).
[0162] (Quantity of -CF2H)
[0163] The number of -CF2H groups in the fluorinated copolymer was determined using an AVANCE-300 nuclear magnetic resonance (NMR) system (manufactured by Bruker BioSpin) at a temperature set to (polymer melting point + 20) °C. 19 The value was determined by F-NMR analysis and obtained from the peak integral of the -CF2H group.
[0164] (The number of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2)
[0165] The dried powders or granules obtained in the examples and comparative examples were cold-pressed to form films with a thickness of 0.25 mm to 0.3 mm. The films were analyzed by scanning them 40 times using a Fourier transform infrared spectroscopy (FT-IR) device (Spectrum One, PerkinElmer) to obtain infrared absorption spectra. The obtained infrared absorption spectra were compared with those of known films to determine the types of terminal groups. Furthermore, based on the absorption peaks of specific functional groups appearing in the differential spectrum between the obtained infrared absorption spectra and those of known films, the concentration of each 1 × 10⁻⁶ functional group in the sample was calculated according to the following formula (A). 6 The number of functional groups N per carbon atom.
[0166] N = I × K / t(A)
[0167] I: Absorbance
[0168] K: Correction coefficient
[0169] t: Membrane thickness (mm)
[0170] For reference, the absorption frequencies, molar absorptivity, and correction factors for the functional groups in the examples are shown in Table 2. Furthermore, the molar absorptivity was determined using FT-IR measurement data from the low-molecular-weight model compounds.
[0171] [Table 2]
[0172] Table 2
[0173]
[0174] (Mel flow rate (MFR))
[0175] Regarding the MFR of fluorinated copolymers, according to ASTM D-1238, the mass (g / 10 min) of polymer flowing out of a die with an inner diameter of 2 mm and a length of 8 mm is measured every 10 minutes using a melt flow index tester G-01 (manufactured by Toyo Seiki Co., Ltd.) at 372°C and a load of 5 kg, and the MFR is calculated accordingly.
[0176] (Melting point)
[0177] Regarding the melting point of the fluorinated copolymer, a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science) was used to perform a first heating from 200°C to 350°C at a heating rate of 10°C / min. Then, the temperature was cooled from 350°C to 200°C at a cooling rate of 10°C / min. A second heating was then performed from 200°C to 350°C at a heating rate of 10°C / min. The melting point was determined from the peak value of the melting curve generated during the second heating process.
[0178] Example 1
[0179] 40.25 kg of deionized water and 0.419 kg of methanol were added to a 174 L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen under vacuum. Afterward, the autoclave was degassed under vacuum, and 40.25 kg of HFP and 0.82 kg of PPVE were added to the vacuum-sealed autoclave. The autoclave was then heated to 25.5 °C. Next, TFE was added until the internal pressure of the autoclave reached 0.970 MPa. Then, 1.25 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.970 MPa, and this pressure was maintained by continuously adding TFE. 0.419 kg of methanol was added 1.5 hours after the start of polymerization. Two hours after the start of polymerization, 1.25 kg of DHP was added, and four hours later, with the internal pressure reduced by 0.002 MPa. Six hours later, 0.96 kg of DHP was added, with the internal pressure reduced by 0.002 MPa each time. Thereafter, 0.25 kg of DHP was added every two hours until the reaction was complete, with the internal pressure reduced by 0.002 MPa each time.
[0180] It should be noted that 0.13 kg of PPVE was added at the points when the TFE addition reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. Additionally, 0.419 kg of methanol was added to the autoclave at the points when the TFE addition reached 6.0 kg and 18.1 kg, respectively. The polymerization was terminated when the TFE addition reached 40.25 kg. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water and dried at 150°C for 10 hours to obtain 43.4 kg of dry powder.
[0181] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Chibei Co., Ltd.) to obtain copolymer granules. The HFP and PPVE contents of the obtained granules were determined using the method described above. The results are shown in Table 3.
[0182] The obtained granules were degassed in an electric furnace at 200°C for 72 hours, then placed in a VVD-30 vacuum vibratory reactor (manufactured by Okawahara Manufacturing Co., Ltd.), and heated to 110°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. This process was repeated 0.5 hours later, followed by another vacuum and introduction of F2 gas. This process of introducing F2 gas and evacuating the vacuum was repeated once every hour, and the reaction was carried out at 110°C for 8 hours. After the reaction was completed, the reactor was completely replaced with N2 gas to stop the fluorination reaction and obtain the granules. Various physical properties of the obtained granules were measured using the above method. The results are shown in Table 3.
[0183] Example 2
[0184] The amount of methanol added before polymerization was changed to 0.526 kg, and the amount of methanol added separately after polymerization started was also changed to 0.526 kg each time. The amount of PPVE added before polymerization was changed to 1.51 kg, and the amount of PPVE added separately after polymerization started was also changed to 0.24 kg each time. Otherwise, copolymer granules were obtained in the same manner as in Example 1. The HFP and PPVE contents of the obtained granules were determined using the methods described above. The results are shown in Table 3.
[0185] The obtained granules were degassed in an electric furnace at 200°C for 8 hours, then placed in a VVD-30 vacuum vibratory reactor (manufactured by Okawahara Seisakusho Co., Ltd.), and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. This process was repeated 0.5 hours later, followed by another vacuum and introduction of F2 gas. This process of introducing F2 gas and evacuating the vacuum was repeated every hour, and the reaction was carried out at 200°C for 8 hours. After the reaction, the reactor was completely replaced with N2 gas to terminate the fluorination reaction, yielding granules. Various physical properties of the obtained granules were measured using the above method. The results are shown in Table 3.
[0186] Example 3
[0187] The amount of methanol added before polymerization was changed to 0.516 kg, and the amount of methanol added separately after polymerization started was also changed to 0.516 kg each time. The amount of PPVE added before polymerization was changed to 1.37 kg, and the amount of PPVE added separately after polymerization started was also changed to 0.22 kg each time. Otherwise, copolymer granules were obtained in the same manner as in Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0188] The resulting granules were fluorinated in the same manner as in Example 2. Using the resulting granules, various physical properties were determined using the methods described above. The results are shown in Table 3.
[0189] Example 4
[0190] The amount of methanol added before polymerization was changed to 0.450 kg, and the amount of methanol added separately after polymerization started was also changed to 0.450 kg each time. The amount of PPVE added before polymerization was changed to 1.09 kg, and the amount of PPVE added separately after polymerization started was also changed to 0.19 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.948 MPa. Otherwise, copolymer granules were obtained in the same manner as in Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0191] The resulting granules were fluorinated in the same manner as in Example 2. Using the resulting granules, various physical properties were determined using the methods described above. The results are shown in Table 3.
[0192] Example 5
[0193] The amount of methanol added before polymerization was changed to 0.124 kg, and the amount of methanol added separately after polymerization started was also changed to 0.124 kg each time. The amount of PPVE added before polymerization was changed to 1.06 kg, and the amount of PPVE added separately after polymerization started was also changed to 0.21 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.906 MPa. Otherwise, copolymer granules were obtained in the same manner as in Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0194] The resulting granules were fluorinated in the same manner as in Example 2. Using the resulting granules, various physical properties were determined using the methods described above. The results are shown in Table 3.
[0195] Example 6
[0196] The amount of methanol added before polymerization was changed to 0.030 kg, and the amount of methanol added separately after polymerization started was also changed to 0.030 kg each time. The amount of PPVE added before polymerization was changed to 0.90 kg, and the amount of PPVE added separately after polymerization started was also changed to 0.19 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.893 MPa. Otherwise, copolymer granules were obtained in the same manner as in Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0197] The resulting granules were fluorinated in the same manner as in Example 2. Using the resulting granules, various physical properties were determined using the methods described above. The results are shown in Table 3.
[0198] Comparative Example 1
[0199] 0.945 kg of deionized water and 0.014 kg of methanol were added to a 4 L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen under vacuum. Then, the autoclave was degassed under vacuum, and 0.945 kg of HFP was added to the vacuum-sealed autoclave. The autoclave was then heated to 25.5 °C. Next, TFE was added until the internal pressure of the autoclave reached 0.970 MPa. Then, 0.029 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.970 MPa and maintained by continuously adding TFE. 0.014 kg of methanol was added 1.5 hours after the start of polymerization. 0.029 kg of DHP was added 2 hours and 4 hours after the start of polymerization, and the internal pressure was reduced by 0.002 MPa each time.
[0200] Additionally, when the amount of TFE added reached 0.141 kg, 0.014 kg of methanol was added to the autoclave. Then, the polymerization was terminated when the amount of TFE added reached 0.473 kg. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water and dried at 150°C for 10 hours to obtain 0.504 kg of dry powder.
[0201] The obtained powder was melt-extruded at 370°C using a 14φ screw extruder (manufactured by Igen Seisakusho) to obtain copolymer granules. The HFP and PPVE contents were determined using the obtained granules according to the above method. The results are shown in Table 3.
[0202] The obtained granules were degassed in an electric furnace at 200°C for 8 hours, then placed in a 500ml portable reactor (TVS1 type, manufactured by a pressure-resistant glass industry company) and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. Then, after another 0.5 hours, a vacuum was applied again, and F2 gas was introduced again. This process of introducing F2 gas and evacuating vacuum was repeated once every hour, and the reaction was carried out at 200°C for 8 hours. After the reaction was completed, the reactor was completely replaced with N2 gas to stop the fluorination reaction, yielding the granules. The obtained granules were used to determine various physical properties using the above method. The results are shown in Table 3.
[0203] Comparative Example 2
[0204] The amount of methanol added before polymerization was changed to 0.749 kg, and the amount of methanol added separately after polymerization started was also changed to 0.749 kg each time. The amount of PPVE added before polymerization was changed to 1.53 kg, and the amount of PPVE added separately after polymerization started was also changed to 0.19 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.994 MPa. Otherwise, copolymer granules were obtained in the same manner as in Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0205] The resulting granules were fluorinated in the same manner as in Example 2. Using the obtained granules, various physical properties were determined by the methods described above. The results are shown in Table 3.
[0206] Comparative Example 3
[0207] The amount of methanol added before polymerization was changed to 0.027 kg, and the amount of methanol added separately after polymerization started was also changed to 0.027 kg each time. The amount of PPVE added before polymerization was changed to 0.61 kg, and the amount of PPVE added separately after polymerization started was also changed to 0.17 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.826 MPa. Otherwise, copolymer granules were obtained in the same manner as in Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0208] The resulting granules were fluorinated in the same manner as in Example 2. Using the resulting granules, various physical properties were determined using the methods described above. The results are shown in Table 3.
[0209] Comparative Example 4
[0210] The amount of methanol added before polymerization was changed to 0.570 kg, and the amount of methanol added separately after polymerization started was also changed to 0.570 kg each time. The amount of PPVE added before polymerization was changed to 1.09 kg, and the amount of PPVE added separately after polymerization started was also changed to 0.19 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.948 MPa. Otherwise, copolymer granules were obtained in the same manner as in Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0211] The resulting granules were fluorinated in the same manner as in Example 1. Using the resulting granules, various physical properties were determined by the methods described above. The results are shown in Table 3.
[0212] Comparative Example 5
[0213] The amount of methanol added before polymerization was changed to 0.374 kg, and the amount of methanol added separately after polymerization started was also changed to 0.374 kg each time. The amount of PPVE added before polymerization was changed to 1.54 kg, and the amount of PPVE added separately after polymerization started was also changed to 0.29 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.924 MPa. Otherwise, copolymer granules were obtained in the same manner as in Example 1. The obtained granules were used without fluorination, and various physical properties were measured using the methods described above. The results are shown in Table 3.
[0214] Comparative Example 6
[0215] The amount of methanol added before polymerization was changed to 0.257 kg, and the amount of methanol added separately after polymerization started was also changed to 0.257 kg each time. The amount of PPVE added before polymerization was changed to 1.12 kg, and the amount of PPVE added separately after polymerization started was also changed to 0.23 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.892 MPa. Otherwise, copolymer granules were obtained in the same manner as in Example 1. The obtained granules were used without fluorination, and various physical properties were measured using the methods described above. The results are shown in Table 3.
[0216] Comparative Example 7
[0217] 945g of deionized water was added to a 4L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen under vacuum. Then, the autoclave was degassed under vacuum, and 945g of HFP and 25.0g of PPVE were added. The autoclave was then heated to 25.5°C. Next, TFE was added until the internal pressure of the autoclave reached 0.892MPa. Then, 29.4g of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.892MPa, and this pressure was maintained by continuously adding TFE. 29.4g of DHP was added 2 hours and 4 hours after the start of polymerization, and the internal pressure was reduced by 0.002MPa each time. 22.6g of DHP was added 6 hours later, and the internal pressure was reduced by 0.002MPa each time. Then, add 1.1g of DHP every 2 hours until the reaction is complete, and reduce the internal pressure by 0.002MPa each time.
[0218] It should be noted that 5.2g of PPVE was added when the continuous addition of TFE reached 190g. Then, polymerization was terminated when the addition of TFE reached 380g. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water, dried at 150℃ for 10 hours, and then dried at 205℃ for 24 hours, yielding 421g of dry powder. The HFP and PPVE contents were determined using the obtained powder according to the above method. The results are shown in Table 3.
[0219] The obtained powder was placed in a portable TVS1 type reactor (manufactured by Pressure Glass Industry Co., Ltd.) and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. Then, after another 0.5 hours, a vacuum was applied again, and F2 gas was introduced again. This process of introducing F2 gas and evacuating the vacuum was repeated every hour, and the reaction was carried out at 200°C for 8 hours. After the reaction was completed, the reactor was completely replaced with N2 gas to stop the fluorination reaction, yielding the powder. Various physical properties of the obtained powder were determined using the above method. The results are shown in Table 3.
[0220] [Table 3]
[0221] Table 3
[0222]
[0223] The "<9" in Table 3 refers to the number of -CF2H groups being less than 9. The "<6" in Table 3 refers to the total number (functional group number N) of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, and -CONH2 being less than 6.
[0224] Next, the obtained granules were used to evaluate the following properties. The results are shown in Table 4.
[0225] (Ozone Exposure Test)
[0226] Fluorinated copolymers were compressed at 350°C under a pressure of 0.5 MPa to produce 1 mm thick sheets, which were then cut into 10 × 20 mm pieces for ozone exposure testing. Ozone gas (ozone / oxygen = 10 / 90 volume%) generated by an ozone generator (trade name: SGX-A11MN (modified), manufactured by Sumitomo Seiki Kogyo Co., Ltd.) was connected to a PFA container filled with ion-exchanged water. Water vapor was added to the ozone gas while the ion-exchanged water was bubbled, and the gas was passed through the PFA tank containing the sample at a rate of 0.7 L / min at room temperature, exposing the sample to the moist ozone gas. After 120 days of initial exposure, the sample was removed, and the surface was gently rinsed with ion-exchanged water. A transmission optical microscope was used to observe the portion from 5 μm to 200 μm below the sample surface at 100x magnification, and the images were taken along with standard measurements. Measurements were taken at 1 mm depth per 1 mm of the sample surface. 2 The number of cracks with a length of 10 μm or more.
[0227] The evaluation will be conducted according to the following criteria.
[0228] ○: The number of cracks is less than 10
[0229] ×: More than 10 cracks
[0230] (Carbon dioxide permeability coefficient)
[0231] Using granulation and a hot press molding machine, sheet-like test pieces with a thickness of approximately 0.1 mm were prepared. Using the obtained test pieces, the carbon dioxide transmittance was measured using a differential pressure gas permeability meter (L100-5000 type gas permeability meter, manufactured by Systech Illinois) according to the method described in JIS K7126-1:2006. The resulting permeability area was 50.24 cm². 2 The carbon dioxide transmittance was measured at a test temperature of 70℃ and a test humidity of 0%RH. Using the obtained carbon dioxide transmittance and the thickness of the test piece, the carbon dioxide transmittance coefficient was calculated using the following formula.
[0232] Carbon dioxide permeability (cm) 3 ·mm / (m 2·24h·atm))=GTR×d
[0233] GTR: Carbon dioxide transmittance (cm) 3 / (m 2 ·24h·atm))
[0234] d: Test piece thickness (mm)
[0235] (Tensile creep test)
[0236] Tensile creep strain was determined using a Hitachi High-Tech TMA-7100. Sheets approximately 0.1 mm thick were prepared using a granulator and thermoforming machine. Samples 2 mm wide and 22 mm long were then fabricated from these sheets. The samples were mounted in the measuring fixture with a 10 mm gap between the clamps. A cross-sectional load of 4.49 N / mm² was applied to the samples. 2 The sample was subjected to a load at 110°C, and the displacement (mm) of its length was measured from 90 minutes to 900 minutes after the start of the test. The ratio of the displacement (mm) to the initial sample length (10mm) was calculated (tensile creep strain (%)). Samples with low tensile creep strain (%) measured at 110°C for 900 minutes do not easily elongate even under prolonged tensile loads in high-temperature environments, demonstrating excellent high-temperature tensile creep resistance (110°C).
[0237] (Creep Resistance Evaluation)
[0238] Creep resistance was determined according to the methods described in ASTM D395 or JIS K6262:2013. A 13mm outer diameter and 8mm height molded body was prepared using granulation and a hot press. Test pieces with an outer diameter of 13mm and a height of 6mm were fabricated from the molded body by cutting. The test pieces were compressed to 50% compression set at room temperature using a compression device. The compressed test pieces were then placed in an electric furnace at 65°C for 72 hours while still fixed in the compression device. The compression device was removed from the furnace, and after cooling to room temperature, the test pieces were removed. The recovered test pieces were left at room temperature for 30 minutes, and their height was measured. The recovery ratio was calculated using the following formula.
[0239] Recovery rate (%) = (t2-t1) / t3 × 100
[0240] t1: Height of the spacer (mm)
[0241] t2: Height of the test piece removed from the compression device (mm)
[0242] t3: Height of compression deformation (mm)
[0243] In the above experiment, t1 = 3.0 mm and t3 = 3.0 mm.
[0244] (Extrusion pressure)
[0245] Extrusion pressure was measured using a RHEOGRAPH 25 dual capillary rheometer (manufactured by Goettfert). A main die inner diameter of 1 mm, L / D = 16, and a secondary die inner diameter of 1 mm, L / D < 1, were used. The measurement temperature was 390°C, the residual heat time after pellet feeding was 10 minutes, and the shear rate was 20 sec. -1 Extrusion was performed for 10 minutes, and the pressure value inside the barrel after extrusion was Bagley corrected, which was then used as the extrusion pressure. Copolymers with low extrusion pressure exhibit excellent extrusion molding properties, injection molding properties, and other molding properties.
[0246] (Conditions for wire coating)
[0247] A coated wire was obtained by extruding a fluorinated copolymer onto a copper conductor with a conductor diameter of 1.00 mm using a 30 mm φ wire coating molding machine (manufactured by Tanabe Plastics Machinery Co., Ltd.). The coating thickness was as follows. The wire coating extrusion molding conditions are as follows.
[0248] a) Core conductor: Conductor diameter 1.00mm
[0249] b) Coating thickness: 0.70mm
[0250] c) Diameter of the covered wire: 2.40mm
[0251] d) Wire pulling speed: 3m / minute
[0252] e) Extrusion conditions:
[0253] • Single-screw extrusion molding machine with a barrel shaft diameter of 30mm and an L / D ratio of 22
[0254] • Die head (inner diameter) / piece (outer diameter) = 24.0mm / 10.0mm
[0255] Extruder set temperatures: Barrel section C-1 (400℃), Barrel section C-2 (375℃), Barrel section C-3 (390℃), Head H (400℃), Die head D-1 (400℃), Die head D-2 (400℃). Core wire preheating is set to 80℃.
[0256] (Changes in outer diameter)
[0257] The outer diameter of the coated wire was measured continuously for one hour using an outer diameter measuring instrument (Zumbach ODAC18XY). The outer diameter value was rounded to three decimal places from the maximum deviation from the specified outer diameter value (2.40 mm), thus determining the variation in outer diameter. The ratio of the absolute value of the difference between the specified outer diameter and the variation in outer diameter to the specified outer diameter (2.40 mm) (the rate of change in outer diameter) was calculated and evaluated according to the following criteria.
[0258] (Rate of change in outer diameter (%)) = |(Change in outer diameter) - (Specified outer diameter)| / (Specified outer diameter) × 100
[0259] ±1%: The variation rate of the outer diameter is less than 1%.
[0260] ±2%: The rate of change in outer diameter exceeds 1% but is less than 2%.
[0261] ×: The rate of change in outer diameter exceeds 2%.
[0262] (Membrane forming properties)
[0263] Using a φ14mm extruder (manufactured by Igen Manufacturing Co., Ltd.) and a T-die, the granules were shaped to form a film. The extrusion molding conditions are as follows.
[0264] a) Winding speed: 1m / minute
[0265] b) Roller temperature: 120℃
[0266] c) Membrane width: 70mm
[0267] d) Thickness: 0.10mm
[0268] e) Extrusion conditions:
[0269] • Single-screw extruder with a barrel diameter of 14mm and an L / D ratio of 20
[0270] Extruder set temperatures: Barrel section C-1 (330℃), Barrel section C-2 (350℃), Barrel section C-3 (365℃), T-die head (370℃)
[0271] The extrusion molding of the fluorinated copolymer was continued until the fluorinated copolymer was stably extruded from the molding machine. Next, a film with a length of 11 m or more (70 mm wide) was produced by extruding the fluorinated copolymer to a thickness of 0.10 mm. A 10-11 m section was cut from the end of the obtained film to prepare a test piece (1 m long, 70 mm wide) for measuring thickness variation. The thickness was measured at three locations: the center point in the width direction at the end of the film and two locations 25 mm away from that center point in the width direction. Furthermore, the thickness was measured at nine locations: three center points spaced 25 cm apart from the center point at one end of the film towards the other end, and two locations 25 mm away from each center point in the width direction. Of the total 12 measurements, one or fewer measurements outside the ±10% range of 0.10 mm were recorded as 0, and two or more measurements outside the ±10% range of 0.10 mm were recorded as ×.
[0272] (Tube Formability)
[0273] Using a φ30mm extruder (manufactured by Tanabe Plastic Machinery), the granules are extruded to form a tube with an outer diameter of 10.0mm and a wall thickness of 1.0mm.
[0274] The extrusion molding conditions are as follows.
[0275] a) Die head inner diameter: 25mm
[0276] b) Outer diameter of the spindle: 13mm
[0277] c) Inner diameter of the shaping mold: 10.5mm
[0278] d) Traction speed: 0.4 m / min
[0279] e) Outer diameter: 10.0mm
[0280] f) Wall thickness: 1.0mm
[0281] g) Extrusion conditions:
[0282] • Single-screw extrusion molding machine with a barrel shaft diameter of 30mm and an L / D ratio of 22
[0283] Extruder set temperatures: Barrel section C-1 (350℃), Barrel section C-2 (370℃), Barrel section C-3 (380℃), Head section H-1 (390℃), Die section D-1 (390℃), Die section D-2 (390℃)
[0284] The obtained tubes are observed and evaluated according to the following criteria. The appearance of the tubes is confirmed visually.
[0285] ○: Good appearance
[0286] ×: The cross-section is not circular; flatness or uneven thickness is observed, indicating a poor appearance.
[0287] (Immersion test in hydrogen peroxide water)
[0288] Using granulation and a hot press molding machine, sheets with a thickness of approximately 0.2 mm were made, and test sheets with a square diameter of 15 mm were prepared. Ten test sheets and 15 g of 3% (w / w) hydrogen peroxide aqueous solution were placed in a 50 mL polypropylene bottle. The solution was heated at 95°C for 20 hours and then cooled to room temperature. The test sheets were removed from the hydrogen peroxide aqueous solution, and TISAB solution (10) (manufactured by Kanto Chemical Co., Ltd.) was added to the remaining hydrogen peroxide aqueous solution. The fluoride ion concentration in the resulting hydrogen peroxide aqueous solution was measured using a fluoride ion meter. The fluoride ion concentration per unit weight of sheet (dissolved fluoride ion concentration) was calculated from the measured value according to the following formula.
[0289] Dissolved fluoride ion concentration (ppm) = Measured value (ppm) × Volume of hydrogen peroxide aqueous solution (g) / Weight of test piece (g)
[0290]
Claims
1. A fluorinated copolymer comprising tetrafluoroethylene units, hexafluoropropylene units, and fluorinated (alkyl vinyl ether) units, wherein, The fluorinated (alkyl vinyl ether) is selected from at least one of the group consisting of perfluorinated (methyl vinyl ether), perfluorinated (ethyl vinyl ether), and perfluorinated (propyl vinyl ether). The content of hexafluoropropylene units relative to all monomer units is 5.0% to 7.5% by mass. The content of fluorinated (alkyl vinyl ether) units is 0.8% to 2.9% by mass relative to all monomer units. The content of tetrafluoroethylene units relative to all monomer units is 89.7%–94.2% by mass. The melt flow rate was 0.7 g / 10 min to 9.5 g / 10 min, which was determined as the mass of polymer flowing out of a die with an inner diameter of 2 mm and a length of 8 mm every 10 minutes at 372 °C and a load of 5 kg. Every 10 6 The number of main chain carbon atoms and the number of functional groups -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH are less than 90.
2. The fluorinated copolymer as described in claim 1, wherein, The content of hexafluoropropylene units is 5.2% to 7.2% by mass relative to all monomer units.
3. The fluorinated copolymer as described in claim 1 or 2, wherein, The content of fluorinated (alkyl vinyl ether) units is 1.2% to 2.2% by mass relative to all monomer units.
4. The fluorinated copolymer as described in claim 1 or 2, wherein, The melt flow rate was 0.7 g / 10 min to 8.0 g / 10 min, which was determined as the mass of polymer flowing out of a die with an inner diameter of 2 mm and a length of 8 mm every 10 minutes at 372 °C and a load of 5 kg.
5. The fluorinated copolymer as described in claim 1 or 2, wherein, The fluorinated (alkyl vinyl ether) unit is a perfluorinated (propyl vinyl ether) unit.
6. An injection-molded article comprising any one of claims 1 to 5.
7. An extruded article comprising the fluorinated copolymer according to any one of claims 1 to 5.
8. A transfer molded article comprising any one of claims 1 to 5 of a fluorinated copolymer.
9. A coated wire having a coating layer comprising a fluorinated copolymer according to any one of claims 1 to 5.
10. A molded article comprising the fluorinated copolymer according to any one of claims 1 to 5, wherein, The molded body is a gasket, wire coating, or film.
Citation Information
Patent Citations
fep with increased bending fatigue strength and low levels of die deposits
JP2004502853A
Modified fluorine-containing copolymer and fluorine resin molded article
CN105849163A
Fluorocopolymer film and its application
CN1715314A
